Original Sin, Currency Depreciation and External Debt Burden: Evidence from India - Augustine, Blessy; Kumar, Lakshmi (International Journal of Economics and Financial Issues, 2020)
Indian Rupee has depreciated around 50 percent against the US Dollar for the last two decades. This depreciating trend generally doesn’t call for any policy interventions as the conventional theories state that it is advantageous for the domestic economy through the competitiveness effect. However, depreciation is expected to increase the external debt burden when the country borrows abroad in foreign currency. At present more than 63 percent of India’s external debt is foreign currency-denominated. Given this, the ramifications of a depreciating rupee through the balance sheet channel invite greater attention. This paper makes an attempt to understand the impact that a depreciating Indian Rupee will have on India’s external debt dynamics. To this end, we estimated an Autoregressive Distributed Lag (ARDL) model using quarterly data for the period 2001-2018. The empirical evidence shows that the depreciation of rupee increases external indebtedness significantly. In the short run, one rupee depreciation increases external debt to GDP ratio by 0.75 percent while in the long run, the increase is 1.26 percent. The study also finds a causal link between external debt and economic growth in the Indian context, which makes the depreciation - debt valuation problem highly relevant. Keywords: External debt, Original Sin, Balance sheet effect, Exchange rate depreciation, India JEL Classifications: F30, F34, H63, H87 DOI: https://doi.org/10.32479/ijefi.9487